PENGARUH PEMANGKASAN CABANG DAN BAKAL BUAH TERHADAP PRODUKSI TANAMAN SEMANGKA (Citrullus vulgaris schard) - Meyco E. Bagunda; Ir. Jemmy Najoan, MS; Tommy B. Ogie, SP., MSi (Universitas Sam Ratulangi, 2019)
ABSTRACT This study aims to determine the effect of interactions between the number of branches and the number of fruit on the production of watermelon plants. The study was carried out in Kalasey 2 Village, Mandolang District, Kab. Minahasa which runs from May to July 2019. This research uses a Randomized Block Design (RBD) consisting of 2 factors. Factor A Number of branches, 1 branch (A1) and 2 branches (A2). Factor B Number of fruits, 1 fruit in 1 branch (B1) 2 fruits in 1 branch (B2) 3 fruits in 1 branch (B3). Thus obtained 6 combinations of treatments A1B1, A1B2, A1B3, A2B1, A2B2, A2B3, the treatment was repeated three times. Observed in this study were fruit weight, fruit diameter, fruit length, and carried out at harvest. The results showed that there was an interaction between the number of branches and the number of fruit on the length and weight of watermelon fruit. Watermelon plants that have 2 branches and 1 fruit (A2B1) produce the heaviest fruit that is 4.63 kg, and the longest fruit that is 27 cm. Then the treatment of 1 fruit (B1) produces the widest fruit diameter that is 56cm. Through this research it is recommended to farmers to get a large fruit size and length and weight, then in 1 plant only retained 1 or 2 watermelons. Keywords : Watermelon, Pruning